Comprehensive method of commercial content Support in the electronic business systems - Vysotska, V.; Chyrun, L.; Chyrun, L. (Видавництво Львівської політехніки, 2013)
In the given article content lifecycle model in electronic commerce systems is proposed. The model describes the processes of information resources processing in the electronic content commerce systems and simplifies the content automation management technology. In the given paper the main problems of e-commerce and content function management services are analyzed.lifecycle, electronic content commerce system. Запропоновано модель життєвого циклу контенту в системах електронної комерції. Модель описує процеси опрацювання інформаційних ресурсів в системах електронної контент-комерції та спрощує технологію автоматизації управління контентом. Проаналізовано основні проблеми електронної комерції та функціональних сервісів управління контентом.
Keywords: information resources; content; content management system; content lifecycle; electronic content commerce system; інформаційний ресурс; контент; система управління контентом; життєвий цикл контенту; система електронної контент-комерції